Protecting pregnancy at work: Normative safety measures and employees' safety strategies in reconciling work and pregnancy. (October 2021) - Abderhalden-Zellweger, Alessia; Probst, Isabelle; Politis Mercier, Maria-Pia; Danuser, Brigitta; Krief, Peggy
Highlights: Contrasting realities with regards to safety measures imposed by regulation. Activity constraints may hinder the implementation of normative safety measures. Some employees' safety strategies can result in negative outcomes. Need to articulate safety regulations and adaptive safety management. Employee involvement and proactivity in matters of occupational health are essential. Abstract: Background: In Switzerland, occupational risks for pregnant workers are covered by specific maternity protection legislation (MPL); however, studies show significant shortcomings in the implementation of these policies among companies. Aims: Analyse the gaps between the provisions of Switzerland's MPL, the protective measures companies plan to take and actual protection practices. We also aim to understand how employees develop their own strategies in order to make up for the shortcomings or contradictions of companies' measures. Methods: Interviews with 46 different stakeholders from organisations in the healthcare sector and the food industry were transcribed and analysed thematically. Results: Some of the organisations used procedures apparently in line with legislation, while others planned more informal approaches to managing on a case-by-case basis. Normative safety measures within the framework of national legislation served as resources for both managers and their employees. However, implementing these measures ran up against real-world workplace constraints, which sometimes rendered them impracticable. Employees adapted some measures considered insufficient or developed their own strategies to reconcile work and pregnancy. Conclusions: Being pregnant is challenging to represent in occupational settings; it is not a disease, but it involves important physical and biopsychosocial changes, which affect women's occupational life. The multidimensional, evolving, and yet temporary nature of pregnancy represents a significant challenge to the implementation of MPL within companies. Linking the normative safety measures stipulated in the legislation with pregnant employees' needs—and their job-related knowledge and skills—could be an interesting pathway towards improving maternity protection at work.